If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 3 = 4(3x + 4) Reorder the terms: 3 + 11x = 4(3x + 4) Reorder the terms: 3 + 11x = 4(4 + 3x) 3 + 11x = (4 * 4 + 3x * 4) 3 + 11x = (16 + 12x) Solving 3 + 11x = 16 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 3 + 11x + -12x = 16 + 12x + -12x Combine like terms: 11x + -12x = -1x 3 + -1x = 16 + 12x + -12x Combine like terms: 12x + -12x = 0 3 + -1x = 16 + 0 3 + -1x = 16 Add '-3' to each side of the equation. 3 + -3 + -1x = 16 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 16 + -3 -1x = 16 + -3 Combine like terms: 16 + -3 = 13 -1x = 13 Divide each side by '-1'. x = -13 Simplifying x = -13
| -x^5-x^3+4x=0 | | 11x+3=4x(3x+4) | | -49-7x=9x+17 | | D-8=12 | | 20=3w-1 | | 4k-9k=10j | | 12x(3x-3)-6x(7x-9)= | | 4(2x+3)=7x+4 | | B(b-7)= | | x^2+18x+19=8x-5 | | 4(10d-4)=64 | | x^2+4x+9=6 | | 10(d-4)=60 | | 3x+2x=4x-8 | | 5(3x+3)=30 | | 2(2m-1)=18 | | 5(m-1)=30 | | 3(5a+2)=36 | | 4(2x)-(x+5)= | | 11u-88=3u | | 3(4x-1)=21 | | 0.5(9x+18)=-1.5(5x)-2(3x+4.5) | | 3x^3+26x^2+35x=0 | | 7w=5w+16 | | 3(3y+5)=5y+25 | | graphy=7+10x | | (x-6)(3x+4)=0 | | y=7+10x | | (1/2)(2x-10)=4 | | x^3-3x^2+9x-54=0 | | x^2-4=6 | | 8(y-5)=6-18 |